2014
DOI: 10.1159/000360527
|View full text |Cite
|
Sign up to set email alerts
|

Topical Retinoids in Skin Ageing: A Focused Update with Reference to Sun-Induced Epidermal Vitamin A Deficiency

Abstract: Vitamin A is an important constituent of the epidermis, where it plays a crucial role in epidermal turnover. A deficiency of epidermal vitamin A may be the consequence of nutritional vitamin A deficiency, exposure to sunlight or any UV source, oxidative stress or chronological ageing. As a consequence, any treatment aiming at increasing epidermal vitamin A would exert a protective effect against these deleterious conditions. Retinoids may counteract some deleterious actions of UV radiation by physical and biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 134 publications
0
26
0
Order By: Relevance
“…Retinol products are over-the-counter alternatives to topical antiageing treatments; however, retinoic acid is not used for topical application because it is registered as a drug, as is the case with synthetic retinoids such as adapalene, tazarotene, and bexarotene. In contrast, retinyl esters, retinol, retinaldehyde, and the oxoretinoids can be used in topical cosmeceutical preparations [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Retinol products are over-the-counter alternatives to topical antiageing treatments; however, retinoic acid is not used for topical application because it is registered as a drug, as is the case with synthetic retinoids such as adapalene, tazarotene, and bexarotene. In contrast, retinyl esters, retinol, retinaldehyde, and the oxoretinoids can be used in topical cosmeceutical preparations [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…RAL has demonstrated its efficacy in treating aging skin with a low incidence of irritation . Sorg and Saurat have shown that human keratinocytes in vitro have the ability to take up RAL to convert it into retinoic acid . Their study demonstrated that topical RAL can be used as a precursor of endogenous retinoids, as it can be converted into storage and active forms of vitamin A.…”
Section: Discussionmentioning
confidence: 98%
“…With age, skin undergoes a complex array of multifactorial biological changes where intrinsic factors influenced by environmental factors are at play. Impairment of the structural integrity of the dermis and fibroblast function, reduced dermal hydration, and loss of tonus and elasticity lead to increased folding, sagging, and emergence of wrinkles . Those features might partially result from a depletion of vitamin A, key component of the epidermis, due to chronic exposure to UV, oxidative stress but also aging and nutritional deficiency .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations